Pengaruh Lingkungan Bisnis terhadap Informasi Akuntansi Manajemen dan Penganggaran Dampaknya terhadap Kinerja Perusahaan - Widia Astuty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2012)
This study aims to find empirical evidence on the effect of the managers perception abfll the b11siness environment on the characteristics of management acco11nting information; find empirical evidence on the effect of the managers perception abo1 e business environment on the characteristics of budgeting; and find empirical evidence on the effect of the managers perception of the environment bisnis/, characteristics of management accounting information, budgeting and the pe,jormance characteristics of a manufacturing fD1pany in Medan lnd11slria/ Estate. The method used is descriptive swvey method and explanalo1y su,vey method. The data 11sed are the pri111a1y data using a questionnaire addressed lo the marketing and production manager and president of the company with a Liker! s scale. This study uses census of the entire population as the uni/ o..Olysis as much as 103 manufacturing companies in Jvledan industrial Estate. Data analysis was used path analysis. The results showed that a) the perception of managers of the business environment affect the characteristics of management accounting information; b) perceptions of managers about the business environment affect the characteristics of budgeting; and c) perceptions of managers about the business environment, characteristics of management accounting information, and budgeta,y characteristics affect the pe1jormance of the company.